ANALISIS TINGKAT PENDAPATAN PETANI GARAM DI KABUPATEN SAMPANG - Moh. Yusuf; Prasetyo Nugroho (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Madura Island or commonly called "salt island" is one of the largest salt producers in Indonesia, where people, especially those around the coast, work as salt farmers. Sumenep Regency, Pamekasan Regency and Sampang Regency are the three largest producers in Madura. The author took one district to be analyzed as research material, namely Sampang Regency, precisely in Pangerangan village. Sampang consists of community salt fields covering an area of ​​4,300 ha with a salt production capacity of 300,000 tons/year. This research focuses on the problems experienced by salt farmers by analyzing the income level of salt farmers in Sampang district. In this case the author focuses on the influence of land area and production costs on the income of salt farmers in Sampang Regency. So in this research the author took a quantitative method to calculate data by conducting field research, looking at the impact, distributing questionnaires offline to farmers, drawing conclusions from the data. It can be concluded that the research results show that land area and production costs have a significant influence on the income of salt farmers in Sampang Regency.